2010
DOI: 10.3109/00952990.2010.495438
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prooxidant–Antioxidant Balance in Chronic Heroin Users in a Single Assay: An Identification Criterion For Antioxidant Supplementation

Abstract: Chronic heroin users can benefit from an antioxidant therapy, and the method currently presented can be used as an identification criterion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Opium is traditionally smoked in Iran recreationally or as a remedy for pain, diarrhea and insomnia (2,3). Opiate abuse is related to oxidative stress that is evaluated separately through oxidants and antioxidants (4).…”
Section: Contextmentioning
confidence: 99%
“…Opium is traditionally smoked in Iran recreationally or as a remedy for pain, diarrhea and insomnia (2,3). Opiate abuse is related to oxidative stress that is evaluated separately through oxidants and antioxidants (4).…”
Section: Contextmentioning
confidence: 99%
“…30,31 Furthermore, drug abusers are at oxidative stress. 32,33 Interestingly, the mRNA expression levels of several anti-oxidant genes significantly decreased in SH-SY5Y cells treated with morphine. 34 It has been reported that oxidative stress plays an important role in drug dependency.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, reports from several groups that levels of AT8 antibody, a biomarker of tau-P, are elevated in postmortem brain in illicit opioid users, even in users under age 30 (Ramage et al, 2005;Anthony et al, 2010;Kovacs et al, 2015;Flanagan et al, 2018), as are levels of APP (Ramage et al, 2005), suggest that individuals with opioid use disorder are at increased risk for developing AD/ADRD. Opioids increase oxidative stress in brain, blood, and body (Zhou et al, 2000;Qiusheng et al, 2005;Arana et al, 2006;Xu et al, 2006;Pereska et al, 2007;Pérez-Casanova et al, 2008;Doyle et al, 2009;Ndengele et al, 2009;Abdel-Zahar et al, 2010;Kovatsi et al, 2010aKovatsi et al, , 2010bCemek et al, 2011;Gutowicz et al, 2011;Sumathi et al, 2011;Deng et al, 2012;Ghazavi et al, 2013;Soykut et al, 2013;Fan et al, 2015;Motaghinejad et al, 2015;Samarghandian et al, 2015;Yun et al, 2015Yun et al, , 2017Lauro et al, 2016;Najafi et al, 2017;Mansouri et al, 2018) and thus could increase Aβ and tau-P syntheses and accumulations via multiple mechanisms described above. In neuronal culture, morphine upregulates GSK3β activity (Masvekar et al, 2015), which could contribute to increased tau-P levels in opioid users.…”
Section: Opioid Use Disordermentioning
confidence: 99%